The Relationship between Ward Manager Conflict Management Strategy and Nurse Job Satisfaction - Reni Rahmawati; Siti Anisah; Lilis Kamilah (JOURNAL EDUCATIONAL OF NURSING(JEN), 2026)
The surgical inpatient ward is a hospital care unit with a high workload and demanding work, which has the potential to cause conflict in the nursing work environment. Conflicts that are not managed properly can have a negative impact on work comfort and reduce nurse job satisfaction. The role of the ward manager in implementing appropriate conflict management strategies is very important in creating a conducive work environment. This study aims to analyze the relationship between the ward managers’ conflict management strategy and nurse job satisfaction in the surgical inpatient ward at Gatot Soebroto Army Hospital. This study implemented a correlational analytic design using a cross-sectional approach. The study involved 47 nurses selected through proportionate stratified random sampling. Data collection was conducted using a conflict management strategy questionnaire and a job satisfaction questionnaire. This study employed both univariate and bivariate analysis. Data analysis was performed using the Chi-square test with a significance level of α = 0.05. The results of the statistical analysis showed a significant relationship between the ward managers’ conflict management strategy and nurse job satisfaction (p < 0.05). It was concluded that the ward manager's implementation of effective conflict management strategies has the potential to increase nurses' job satisfaction. Therefore, hospital management is encouraged to strengthen the conflict management competencies of ward managers to promote a harmonious work environment and improve the quality of nursing care.